1972
DOI: 10.1111/j.1471-4159.1972.tb01382.x
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic Activity and Basic Protein Loss in and Around Multiple Sclerosis Plaques: Combined Biochemical and Eiistochemical Observations

Abstract: This combined histochemical and biochemical study has shown that acid proteinase activity (PH 3.5) is increased around histologically-defined active plaques of multiple sclerosis (MS). Biochemical estimation showed that the enzyme is more active in most samples of 'normal' white matter in MS than in controls. A gradient of enzyme activity was observed : control white matter-white matter distant from plaqueclose white matter-edgsplaque. Both electrophoretic and histochemical techniques revealed a reduction or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
47
0

Year Published

1975
1975
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(49 citation statements)
references
References 34 publications
2
47
0
Order By: Relevance
“…Many studies have shown that acid proteases and other lysosomal enzymes are increased around active MS plaques (3-9, 36, 37) and in the central nervous system in EAE (10)(11)(12)(13)(14)(15). The increase in acid proteases in plaques correlates with the decrease in BP (5,6) which is known to be readily digested by proteases (13,38,39). However, neutral and acid protease activities were elevated to a similar degree in the spinal cord of rats with EAE (40).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that acid proteases and other lysosomal enzymes are increased around active MS plaques (3-9, 36, 37) and in the central nervous system in EAE (10)(11)(12)(13)(14)(15). The increase in acid proteases in plaques correlates with the decrease in BP (5,6) which is known to be readily digested by proteases (13,38,39). However, neutral and acid protease activities were elevated to a similar degree in the spinal cord of rats with EAE (40).…”
Section: Methodsmentioning
confidence: 99%
“…However, the mechanism by which the inflammatory cells, predominantly macrophages and lymphocytes in MS and EAE, participate in the process of demyelination has not yet been defined. Most attention has been directed toward acid proteases and lysosomal hydrolases which increase in and around MS plaques (3)(4)(5)(6)(7)(8)(9) and in lesions in animals with EAE (10)(11)(12)(13)(14)(15). It has…”
mentioning
confidence: 99%
“…However, in multiple sclerosis and other demyelinating conditions there is primary dissolution of the myelin lamellae, with early loss of basic protein. As this protein is susceptible to proteolysis, proteinases have been implicated in the demyelinating process (Einstein et al, 1972;Adams et al, 1971). Previous studies on isolated myelin showed that the basic protein was partially lost on treatment with trypsin, but unexpectedly the myelin-sheath ultrastructure appears to be unaltered (Raghavan et al, 1973;Wood et al, 1974).…”
mentioning
confidence: 99%
“…As one example, the envelope proteins of Semliki forest virus, which interact hydrophobically with the viral lipid bilayer, can be almost completely hydrolyzed by proteolytic enzymes, leaving a small hydrophobic polypeptide fragment which is the part of the protein embedded in the bilayer [ 18,191. Furthermore, in certain pathological conditions, such as multiple sclerosis, the basic CNS myelin protein Al is susceptible to proteolytic attact, at least with cerebral acid proteinase [20], suggesting some alteration in the myelin structure.…”
Section: Discussionmentioning
confidence: 99%